Implementasi Hukum Terhadap Kedudukan Alat Bukti Dalam Hukum Acara Perdata - Iwan Wahyudi (Journal on Education, 2025)
Basically, the evidentiary system is a regulation regarding the type of evidence that can be used, the description of the evidence, and the ways in which the evidence is used and the way the judge must form his beliefs before the court. Evidence is one of the most important aspects brought in and prepared by the parties (Plaintiff and Defendant) in proving the truth of a legal event. Viewed from the parties in the case, evidence can be interpreted as a tool or effort that can be used by the parties in the case to convince the judge before the court. When viewed from the perspective of the court examining the case, evidence means tools or efforts that can be used by the judge to decide the case. So, this evidence is needed by justice seekers and also by the court. A dispute or case cannot be resolved without evidence, meaning that if the plaintiff's claim is not based on evidence then the case will also be decided by the judge but by rejecting the claim because it is not proven. The evidence presented by the parties in court varies, including written evidence, witness statements, allegations, confessions and oaths.